2022
DOI: 10.1002/mp.15625
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of 4D log file‐based proton dose reconstruction for interplay assessment considering amplitude‐sorted 4DCTs

Abstract: Purpose The unpredictable interplay between dynamic proton therapy delivery and target motion in the thorax can lead to severe dose distortions. A fraction‐wise four‐dimensional (4D) dose reconstruction workflow allows for the assessment of the applied dose after patient treatment while considering the actual beam delivery sequence extracted from machine log files, the recorded breathing pattern and the geometric information from a 4D computed tomography scan (4DCT). Such an algorithm capable of accounting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 70 publications
(93 reference statements)
0
19
0
Order By: Relevance
“…Moreover, Spautz et al. showed that the gamma scores were maintained at more than 95% at 3%/3 mm for the time stamp shifts within 5 ms from 10 to 30 mm motion 36 . The spot response time results from the acceptance test conducted by the vendor showed that our 4DDD calculation system could be completely controlled in less than 20 ms, including the delay of the trigger signal.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Moreover, Spautz et al. showed that the gamma scores were maintained at more than 95% at 3%/3 mm for the time stamp shifts within 5 ms from 10 to 30 mm motion 36 . The spot response time results from the acceptance test conducted by the vendor showed that our 4DDD calculation system could be completely controlled in less than 20 ms, including the delay of the trigger signal.…”
Section: Discussionmentioning
confidence: 87%
“…Besides the dose calculation accuracy and divided spot assignment in the TPS, uncertainties arise from the deformation accuracy of the DIR. Factors affecting the dose deformation of the reference CT include deformation grid sizes, time resolution of the 4DCT phases for dividing spots, CT value variations between 4DCT phases, and the deformation algorithm 36,37 . Ribeiro et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 4DDCs are clearly indispensable for 4D optimization (Keall et al 2006, West et al 2007, Eley et al 2014, Graeff 2014, Bernatowicz et al 2017, Graeff 2017. Different 4DDC approaches have also been experimentally validated (Bert et al 2009, Testa et al 2013, Krieger et al 2018, Pfeiler et al 2018, Kostiukhina et al 2020, Spautz et al 2022.…”
Section: Introductionmentioning
confidence: 97%